Aproximación cuantitativa de los efectos de la competencia en la contratación estatal: evidencia de Colombia (2020)
Because of the importance of public procurement for the economy and the unquestionable need to optimize public resources, this study evaluates the effect of competition in public procurement, which we capture through an awarding coefficient. We apply fixed effects to our sample and some subsets. The findings of our study reveal that one additional competitor improves economic efficiency in a percentage oscillating between 0.58% and 1.33%. This efficiency improvement can be read as savings for the Colombian government. The results for minimum quantity contracts are comparatively more pronounced and statistically significant, while for public tenders and abbreviated selection processes, the results are less robust. However, for these last public procurement procedures, the coefficient of the variable SameCity is positive and significant. This result suggests that public procurement procedures in which the awarded competitor comes from a different city from that where the public procurement is developed, are more exposed to competitive pressures. Likewise, we found evidence that suggests that public procurement at the national level for these two last public procurement procedures, would be comparatively more competitive than public procurement procedures at the local level. In conclusion, the evidence for Colombia shows that a more competitive environment is positively related to economic efficiency? and is negatively related to the awarding coefficient? in public procurement. Therefore, policies that more decisively promote a plurality of competitors are recommended. Other public policy recommendations are described in the present study, as well.